Practical Identification of Emotional Meaning Based on Collocational Analysis - Sobirova, Gulzora Sattorovna (The Lingua Spectrum, 2026)
Emotional meaning is an important component of linguistic communication because speakers constantly express feelings, attitudes, and evaluations through language. While traditional linguistic studies often focus on words that directly denote emotions, modern approaches emphasize the role of lexical interaction in forming emotional meaning. This article investigates the practical identification of emotional meaning in English through collocational analysis of lexical units. The research combines corpus-based analysis with discourse examples from literary texts and media sources. The data were collected from authentic texts and linguistic corpora such as the British National Corpus and the Corpus of Contemporary American English. Particular attention is given to structural patterns of emotional collocations, including adjective-noun, verb-noun, and adverb-adjective combinations. The results demonstrate that emotional meaning frequently emerges from regular patterns of lexical co-occurrence rather than from isolated lexical items. The study also discusses the pedagogical and linguistic implications of collocational analysis for vocabulary teaching and second language learning.